Physical and functional interaction of the archaeal single-stranded DNA-binding protein SSB with RNA polymerase - Richard, Derek J. (Oxford University Press, 2004)
Archaeal transcription utilizes a complex multisubunit RNA polymerase and the basal transcription factors TBP and TF(II)B, closely resembling its eukaryal counterpart. We have uncovered a tight physical and functional interaction between RNA polymerase and the single-stranded DNA-binding protein SSB in Sulfolobus solfataricus. SSB stimulates transcription from promoters in vitro under TBP-limiting conditions and supports transcription in the absence of TBP. SSB also rescues transcription from repression by reconstituted chromatin. We demonstrate the potential for promoter melting by SSB, suggesting a plausible basis for the stimulation of transcription. This stimulation requires both the single-stranded DNA-binding domain and the acidic C-terminal tail of the SSB. The tail forms a stable interaction with RNA polymerase. These data reveal an unexpected role for single-stranded DNA-binding proteins in transcription in archaea.